Quotient operators: new generation of linear operators - Gherbi, Abdellah; Messirdi, Bekkai; Benharrat, Mohammed (Funct. Anal. Approx. Comput, 2015)
In this paper we attempt to investigate some algebraic and topological properties of quotient operators acting on Hilbert space, and to give a characterization of Fredholm quotient operator and its index.
Keywords: Quotient operator; closed range; generalized inverse; normal operator; nilpotent; idempotent; compact and Fredholm